NETWORK DIVERSIFICATION: ECONOMIC ANALYSIS AND STRATEGIES: https://doi.org/10.5281/zenodo.14718163 - Sunnatov , Qudratulla (Journal of Contemporary World Studies, 2025)
This article examines the economic analysis of network diversification, its benefits and limitations, and the strategies used in different countries. Network diversification is important in reducing economic risks, creating innovative opportunities, and expanding markets. The article analyzes the vertical and horizontal forms of diversification, as well as the role of diversification in increasing economic efficiency and stability for companies. However, the diversification process has limitations such as management difficulties, misallocation of resources and high investment costs. The article provides recommendations for the implementation of successful diversification strategies by in-depth study of the economic and strategic aspects of network diversification.